Pengaruh Kompensasi dan Beban Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Mediasi (Survei pada Karyawan PT. Andalan Dua Satu Ekspres Cabang Surabaya) - Wahyu Priatmoko, Brilly; Fii Ahsani, Riska (Teewan Journal Solutions, 2025)
Business people must be able to maintain their company's position in increasingly tight global marketing in both services and goods. Business people think hard to maintain their position in the business to win the competition through determining the right strategy by utilizing their human resources. The purpose of this study was to analyze the significance effect of compensation and workload on employee job satisfaction, significance effect of workload on employee job satisfaction, analyze the significance effect of job satisfaction, compensation and workload on employee performance and analyze the significance effect of compensation and workload on employee performance with job satisfaction as a mediating variable.This research was conducted on employees of PT Andalan Dua Satu Ekspres Surabaya Branch with survey techniques. The study population was 96 employees so that all of them became research samples with saturated sampling technique. Data collection techniques used questionnaires. Data analysis techniques using multiple linear regression, t test, F test, coefficient of determination and sobel test. The results showed that compensation has a positive and significant effect on employee job satisfaction. Workload has a negative and significant effect on employee job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Compensation has a positive and significant effect on employee performance. Workload has a negative and significant effect on employee performance. Compensation has a significant effect on employee performance with job satisfaction as a mediating variable. Workload does not have a significant effect on employee performance with job satisfaction as a mediating variable.